Dual-functional witherite in improving chemical looping performance of iron ore and simultaneous adsorption of HCl in syngas at high temperature - Wang, Haiming (2022)
The synergetic effect in using witherite (BaCO3) and iron ore (IO) for simultaneous dechlorination and chemical looping combustion (CLC) of municipal solid waste (MSW) derived syngas was studied on a bench-scale fluidized bed reactor at the temperature range of 800–900 °C. For comparison, limestone a widely used HCl sorbent was also tested. It was found that the pristine IO had negligible HCl sorption capacity during CLC of syngas. The IO-witherite mixture demonstrated much higher HCl adsorption capacity than the pristine IO and IO-limestone mixture in the temperature range of 800 to 900 °C with the presence of 25–35 vol% H2O in syngas. At the loading ratio 10 wt% of sorbent, the HCl removal capacity of IO-witherite was 3 times higher than that of the IO-limestone at 900 °C. Though IO and sorbent were physically mixed, a strong solid-solid interaction between IO and witherite surface occurred to form interstitial solid solution, BaFe12O19. The hexagonal structure of the BaFe12O19 facilitated the lattice oxygen mobility and thus improved greatly the redox performance of the IO. With increasing the inlet HCl concentration, the CLC performance of IO-Ba was further improved mainly because the chlorination process made the witherite particles more porous, which benefits the solid-solid interactions. The bulk spent witherite particles after processing could be separated easily from the IO particles by magnetic separation to realize the recovery of the used sorbents, while IO particles could be refilled into the CLC process. This research highlights that the IO-witherite mixture could be a promising OC for the CLC of HCl containing syngas to accomplish cleaner combustion.